Penerapan Motif Ukiran Minangkabau Sebagai Jam Hias - Febri Darul Islam; Asra IIal Khairi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The aim of making this work is to visualize the meaning contained in Minangkabau motifs in carvings using surian wood as a three-dimensional work with the theme being the lessons we take from everyday life. The method used in making this work goes through several stages, namely: (1). Preparation Stages, (2). Elaboration Stages, (3). Synthesis Stages, (4). Concept Realization Stages, (5). Finishing stages The results of the works that have been visualized in two-dimensional media have been developed resulting in the titles kaluak Paki,